Accounts payable turnover and firm performance of quoted manufacturing firms in Nigeria - Oranefo, Patricia Chinyere; Egbunike, Chinedu Francis (Goodwood Publishing, 2023)
Purpose: The objective of this study is to ascertain the nexus of accounts payable turnover and firm performance of quoted manufacturing firms in Nigeria. Research methodology: This study adopted an ex-post facto research design. The sample comprised seventy-five non-financial firms quoted on the Nigerian Exchange Group (NGX). The study purposively selected all available non-financial firms during the study period: 2010-2019. This study utilized secondary sources of data, i.e., computed financial ratios from annual financial statements downloaded from the MachameRatios® database. The data were analyzed using multiple regression techniques. Results: There is a non-significant positive effect of the accounts payable turnover ratio on ROA (p=0.9729) and ROE (p=0.2669); and; a significant negative effect of the accounts payable turnover ratio on Tobin’s Q (p=0.0140). Conlusion:Accounts payable turnover has no significant effect on ROA and ROE but negatively affects Tobin’s Q. This highlights its limited impact on accounting returns but notable influence on market value. Strategic management of payables remains essential. Limitations: The limitation of the study is the failure to account for endogeneity concerns in firm performance studies. Contribution: The study contributes to the working capital management literature and specifically to the credit management axiom. It also showed a differential effect of APT on various firm performance proxies which have significant implications for managers, e.g., finance officers in corporations that intend to utilize the accounts payable turnover as a strategy to grow the performance of the firm in the short and long term.